An agile planning and operations framework. Issue 2 (9th July 2018) - Jaggars, Damon; Jones, DeEtta
Abstract : Purpose: The purpose of this paper is to describe the design and implementation of an agile planning and operations framework for an academic research library, designed to facilitate an ongoing organizational conversation about the organization's strategic intent and how it plans to move from intention to reality. The goals motivating the implementation of such a framework include creating iterative, open-ended planning and management processes that enable increased flexibility and openness to unforeseen opportunities, as well as the ongoing integration of library faculty, staff, and external stakeholder voices into planning, management, and assessment discussions. Design/methodology/approach: The framework seeks to harmonize planning, management, and assessment processes over 18-24-month rolling time horizons, during which organizational efforts and investments would be reviewed and revised in an iterative fashion. Findings: The authors share results and analyses from stakeholder assessments used to develop foundational mission, vision, values, and strategic directions documentation and discuss the structural, cultural, and organizational development challenges confronted and gains experienced in implementing the framework. Originality/value: Many academic libraries are exploring new approaches to strategic planning, ways to enhance organizational health, and manage change. The authors are unaware of an academic or research library that has attempted to design and implement a similar approach to strategic planning and its assessment. The agile planning framework provides an alternative to traditional "waterfall" approaches to strategic planning for libraries.